2019
DOI: 10.3390/cells8121565
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Maintains Muscle Homeostasis through the Novel Shuttle Pathway of Thyroid Hormones during Myoblast Differentiation

Abstract: Skeletal muscle, the largest part of the total body mass, influences energy and protein metabolism as well as maintaining homeostasis. Herein, we demonstrate that during murine muscle satellite cell and myoblast differentiation, transthyretin (TTR) can exocytose via exosomes and enter cells as TTR- thyroxine (T4) complex, which consecutively induces the intracellular triiodothyronine (T3) level, followed by T3 secretion out of the cell through the exosomes. The decrease in T3 with the TTR level in 26-week-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The developmental process of multinucleated myofibers with contractile capability from MSCs is termed myogenesis, and involves cell cycle arrest, cell fusion, increases in nuclear sizes, and the peripheral localization of nuclei (Charge and Rudnicki, 2004). Myogenesis is a decidedly regulated mechanism that is determined by the co-expressions of Pax3, Pax7, and myogenicregulatory factors such as Myf5, Mrf4, MyoD, and myogenin in MSCs (Zammit and Beauchamp, 2001;Relaix et al, 2005;Baig et al, 2019;Kim et al, 2019;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The developmental process of multinucleated myofibers with contractile capability from MSCs is termed myogenesis, and involves cell cycle arrest, cell fusion, increases in nuclear sizes, and the peripheral localization of nuclei (Charge and Rudnicki, 2004). Myogenesis is a decidedly regulated mechanism that is determined by the co-expressions of Pax3, Pax7, and myogenicregulatory factors such as Myf5, Mrf4, MyoD, and myogenin in MSCs (Zammit and Beauchamp, 2001;Relaix et al, 2005;Baig et al, 2019;Kim et al, 2019;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, in SS, in both muscles, our results indicate a significant down-representation of transthyretin (TTR), the transporter protein for T 4 in the blood ( 39 42 ). The liver is considered the main contributing organ for TTR release, but a recent study has shown TTR synthesis in muscle cells, where the protein has been suggested to exocytose through exosomes and bring back T 4 inside the cells for conversion to T3 ( 43 ). The reduced representation levels of TTR in tibialis anterior and soleus of SS animals appear coherent with a locally reduced T3 bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…FNDC5 was initially introduced as a regulator of myoblast differentiation (Ferrer-Martinez et al, 2002). Fndc5 knockdown in muscle stem cells decreased the expression of myogenic genes and myotube formation without any effects on muscle growth (Lee et al, 2019). Recently, it was shown that inhibiting Fndc5 expression induces autophagy and causes skeletal muscle atrophy (Pan et al, 2019).…”
Section: Skeletal Musclementioning
confidence: 99%